Chitinase Chit62J4 Essential for Chitin Processing by Human Microbiome Bacterium Clostridium paraputrificum J4 - Dohnálek, Jan; Dušková, Jarmila; Tishchenko, Galina; Kolenko, Petr; Skálová, Tereza; Novák, Petr; Fejfarová, Karla; Šimůnek, Jiří (Molecules, 2021)
Commensal bacterium Clostridium paraputrificum J4 produces several extracellular chitinolytic enzymes including a 62 kDa chitinase Chit62J4 active toward 4-nitrophenyl N,N'-diacetyl-β-d-chitobioside (pNGG). We characterized the crude enzyme from bacterial culture fluid, recombinant enzyme rChit62J4, and its catalytic domain rChit62J4cat. This major chitinase, securing nutrition of the bacterium in the human intestinal tract when supplied with chitin, has a pH optimum of 5.5 and processes pNGG with Km = 0.24 mM and kcat = 30.0 s-1. Sequence comparison of the amino acid sequence of Chit62J4, determined during bacterial genome sequencing, characterizes the enzyme as a family 18 glycosyl hydrolase with a four-domain structure. The catalytic domain has the typical TIM barrel structure and the accessory domains-2x Fn3/Big3 and a carbohydrate binding module-that likely supports enzyme activity on chitin fibers. The catalytic domain is highly homologous to a single-domain chitinase of Bacillus cereus NCTU2. However, the catalytic profiles significantly differ between the two enzymes despite almost identical catalytic sites. The shift of pI and pH optimum of the commensal enzyme toward acidic values compared to the soil bacterium is the likely environmental adaptation that provides C. paraputrificum J4 a competitive advantage over other commensal bacteria.
Keywords: střevní mikroflóra; koncentrace vodíkových iontů; Chitin; Humans; chitinasy; Catalytic Domain; Chitinases; Clostridium; bakteriální proteiny; Gastrointestinal Microbiome; Recombinant Proteins; Hydrogen-Ion Concentration; rekombinantní proteiny; lidé; chitin; Bacterial Proteins; katalytická doména